Strategy for Designing English Language Resource-Based Learning Materials in the Moodle LMS - Rizky Eka Prasetya (Universitas Dian Nuswantoro, 2022)
Abstract. This research examines resource-based learning (RBL) strategy in teaching and learning English as a foreign language in Moodle LMS contexts. This research is exploratory case studies approach in qualitative research design—the sample of this research is 36 English lecturers from five south Jakarta higher education institutions. The data were gathered using online interviews and focus group discussions and analyzed by thematic analysis. The findings show that accommodated strategy uses Resource-Based Learning involved learning objectives; structure, organization, and instructional design; by doing - through repetition, practice, try, and mistake; structured feedback is built-in for English language learners; and introductions, overviews, and evaluations. English lecturers and instructors must lead and promote learning via proper RBL strategies. Given the increased availability of resources and their flexibility in handling and use, it appears appropriate to transition toward a resource-based approach. Online exploration of Moodle features, RBLE preparatory components, and English language teaching possibilities. Moreover, the preparation components for designing RBL Instructions are contexts, instruments, and scaffolds. In conclusion, English lecturers and instructors must lead and promote learning via proper RBL strategies. Given the increased availability of resources and their flexibility in handling and use, it appears appropriate to transition toward a resource-based approach. Online exploration of Moodle features, RBL preparatory components, and English language teaching possibilities. For this group of educators, more research may reveal what form of online media infrastructure they need, both individually and as a group, to support the knowledgeability of the RBL model's efficacy.Keywords: designing strategy; English language; English language teaching; resource-based learning; Moodle LMS.Abstrak. Penelitian ini bertujuan untuk mengkaji penerapan pembelajaran berbasis sumber (Resource Based Learning-RBL) dalam konteks belajar mengajar bahasa Inggris sebagai bahasa asing dalam konteks Moodle LMS. Penelitian ini menggunakan pendekatan studi kasus eksploratif dengan desain penelitian kualitatif—sampel penelitian ini adalah 36 dosen bahasa Inggris dari lima perguruan tinggi di Jakarta Selatan. Data dikumpulkan dengan menggunakan wawancara daring dan diskusi kelompok terfokus dan dianalisis dengan analisis tematik. Temuan menunjukkan bahwa strategi yang diakomodasi menggunakan Pembelajaran Berbasis Sumber Daya melibatkan tujuan pembelajaran; struktur, organisasi, dan desain instruksional; dengan melakukan - melalui pengulangan, latihan, percobaan, dan kesalahan; umpan balik terstruktur adalah bawaan untuk pelajar bahasa Inggris; dan pendahuluan, ikhtisar, dan evaluasi. Dosen dan instruktur bahasa Inggris harus memimpin dan mempromosikan pembelajaran melalui strategi RBL yang tepat. Mengingat ketersediaan sumber daya yang meningkat dan keluwesannya dalam penanganan dan penggunaan, tepat untuk beralih ke pendekatan berbasis sumber daya. Eksplorasi daring fitur Moodle, komponen persiapan RBL, dan kemungkinan pengajaran bahasa Inggris. Selain itu, komponen persiapan untuk merancang instruksi RBL adalah konteks, instrumen, dan perancah. Kesimpulannya, dosen dan instruktur bahasa Inggris harus mengedepankan dan meningkatkan pembelajaran melalui strategi RBL yang tepatKata kunci: strategi desain; bahasa Inggris; pengajaran bahasa Inggris; pembelajaran berbasis sumber daya; LMS Moodle